2020
DOI: 10.3389/fonc.2020.580112
|View full text |Cite
|
Sign up to set email alerts
|

Breast Subtypes and Prognosis of Breast Cancer Patients With Initial Bone Metastasis: A Population-Based Study

Abstract: BackgroundMetastatic breast cancer (MBC) is a highly heterogeneous disease and bone is one of the most common metastatic sites. This retrospective study was conducted to investigate the clinical features, prognostic factors and benefits of surgery of breast cancer patients with initial bone metastases.MethodsFrom 2010 to 2015, 6,860 breast cancer patients diagnosed with initial bone metastasis were analyzed from Surveillance, Epidemiology, and End Results (SEER) database. Univariate and Multivariable analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 43 publications
7
42
2
Order By: Relevance
“…These numbers are supported by other reports covering the same period for Danish and international cohorts [8][9][10][11][12][13]. Survival rates are likely to have improved since then [14][15][16], but bone metastasis remains an incurable condition. Contributing to the poor prognosis are the consequences of bone metastases such as anemia, increased susceptibility to infection, life-threatening hypercalcemia, spinal cord compression, severe pain, fatigue, increased risk of skeletal fractures, and decreased mobility [17][18][19][20].…”
Section: Introductionsupporting
confidence: 65%
“…These numbers are supported by other reports covering the same period for Danish and international cohorts [8][9][10][11][12][13]. Survival rates are likely to have improved since then [14][15][16], but bone metastasis remains an incurable condition. Contributing to the poor prognosis are the consequences of bone metastases such as anemia, increased susceptibility to infection, life-threatening hypercalcemia, spinal cord compression, severe pain, fatigue, increased risk of skeletal fractures, and decreased mobility [17][18][19][20].…”
Section: Introductionsupporting
confidence: 65%
“…Nomogram modelling has been used effectively in a number of studies. 29,30 We recommend that patients who are judged to be at high risk using our diagnostic model should have supplemental CT scans before surgery to confirm the diagnosis and rule-out abdominal metastasis of GBC. Additionally, compared with artificially assigning risk factors, assigning corresponding weights to variables through statistical methods may result in more objective extraction of information from clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…All the indicators included in our model can be obtained through physical examination of outpatient. Modelling by using nomograms has been used in a number of studies and has been shown to be effective [29] [30]. We recommend that patients who are judged to be at high risk through our diagnostic model could be supplemented with CT scans before surgery to further con rm the diagnosis and rule out gallbladder cancer abdominal metastasis.…”
Section: Discussionmentioning
confidence: 99%